LIFESTYLE FACTORS AND OBESITY AMONG ADOLESCENTS IN RURAL SOUTH INDIA - MITHRA P, PRASANNA; KUMAR, PAWAN; G KAMATH, VEENA; KAMATH, ASHA; B, UNNIKRISHNAN; T, REKHA; KUMAR, NITHIN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: To estimate the prevalence of obesity among adolescents of thestudy area and to study the association of physical activity, dietary habits with obesity. Methods: This was a school based cross sectional study conducted among 2963 adolescents in Udupi. They were interviewed using pre-tested questionnaire, followed by body mass index measurement and classification using World Health Organization criteria. Statistical analysis was done using Mann–Whitney U-test, Kruskal–Wallis test, and Chi-square tests. Results: The prevalence of overweight was 2.4% and obesity 1.4% and they were higher among the adolescents belonging to higher socio-economic status, among those using motorized transport. Furthermore, 93.2% of the subjects consumed readymade food items apart from homemade ones, 28.8% of them had the habit of eating in between the regular meals, and 59.6% of the subjects had the habit of consuming carbonated beverages regularly. Conclusions: Current levels of obesity and lifestyle factors among the adolescents in the study area can significantly predispose them to the risk of non-communicable diseases, which needs to be considered while making policies for non-communicable diseases. Keywords: Adolescents, Obesity, Overweight, Lifestyle, Diet, World Health Organization.